On the Road to the Split of the American Labor Movement: Criticism of the American Federation of Labor In Committee for Industrial Organizations Pamphlets (1935–1936) - Kowalski , Kamil (Studia Historiae Oeconomicae, 2024)
The US labor movement gained momentum after the passage of the NIRA (1933) and especially the Wagner Act (1935). The new law guaranteed employees the right to organise and bargain collectively through representatives of their own choosing. The dynamic growth in union membership was accompanied by a heated debate over whether unions should be organised to cover all workers in an industry or on an occupational or craft basis. This piece covers Committee of Industrial Organizations (CIO) pamphlets published between 1935 and 1936, a critical period in the rivalry between the American Federation of Labor (AFL) and the CIO. Most took the form of journalistic commentary on current events in the union environment. The pamphlet, as a form of communication, by definition, presents a one-sided description of reality. Nevertheless, the CIO pamphlets are a valuable source of knowledge about the division in the American labor movement in the 1930s. In this piece, I examine the axes of contention and arguments. They cover various issues, such as an assessment of the US trade union movement’s achievements, jurisdictional claims, industrial charters, and dues. I trace the evolution of radicalism in the views of the CIO leadership, from reforming the Committee in the spirit of “unionising unorganised mass production under the banner of the AFL” to massive criticism of the Federation that ultimately made further coexistence impossible. The latter resulted in the AFL suspending the CIO in September 1936.